THE EFFECT OF INCREASE IN THE NUMBER OF FISHING TRIPS ON THE ECONOMIC EFFICIENCY OF 9.82 AND 11 M FISHING TRAWLERS ALONG KERALA COAST - IYER, H KRISHNA; UNNITHAN, G R; RAO, P S; RAO, C.C PANDURANGA; NAIR, R G (Fishery Technology, 2017)
Cost benefit analysis of a 9. 82 m and 11 m fishing trawlers based on the number of fishing trips is presented. The number of fishing trips per year determines the profit and loss of the trawler. With the increase in the number of fishing trips, the profit also increase for both the sizes of trawlers. The minimum quantity of prawn and fish to be landed for 0-20% profit for varying number of fishing trips are worked out. The break-even for 9.82 and 11 m trawlers was observed to be 185 and 210 fishing trips respectively during 1980-81.